THEORETICAL ANALYSIS OF FLOW OF NANOFLUID OVER A STRETCHING SURFACE - JOY, R. ANGEL; VISUVASAM, J.; RAJENDRAN, V.; RAJENDRAN*, L. (International Journal of Mathematical Archive, 2018)
This is the first paper for the application of homotopy analysis method (HAM) in boundary layer flow of nanofluids on stretching sheet. The model used for the nanofluid incorporates the effects of Brownian motion and thermophoresis. The system of nonlinear equations is solved using HAM. An analytical solution is presented which depends on the Prandtl number Pr, Lewis number Le, Brownian motion parameter Nb and thermophoresis parameter Nt. The variation of the reduced Nusselt and reduced Sherwood numbers with Nb and Nt is also presented in tabular forms. The effects of various parameters on the stream function, temperature distribution and volume fraction of nanofluid are also discussed.